Transcriptional and Translational Differences of Microglia from Male and Female Brains - Dilansu Guneykaya (Cell Reports, 2018)
Summary: Sex differences in brain structure and function are of substantial scientific interest because of sex-related susceptibility to psychiatric and neurological disorders. Neuroinflammation is a common denominator of many of these diseases, and thus microglia, as the brain’s immunocompetent cells, have come into focus in sex-specific studies. Here, we show differences in the structure, function, and transcriptomic and proteomic profiles in microglia freshly isolated from male and female mouse brains. We show that male microglia are more frequent in specific brain areas, have a higher antigen-presenting capacity, and appear to have a higher potential to respond to stimuli such as ATP, reflected in higher baseline outward and inward currents and higher protein expression of purinergic receptors. Altogether, we provide a comprehensive resource to generate and validate hypotheses regarding brain sex differences. : Guneykaya et al. provide transcriptomic, proteomic, and functional data from male and female microglia, providing a resource for further investigation of sex-based differences in microglia. Keywords: microglia, sex differences, transcriptomics, proteomics